Análisis del impacto social, económico y financiero del proyecto del Sistema de Riego para la comunidad de Pisambilla, parroquia Cangahua, cantón Cayambe provincia Pichincha - Peña Reinoso, Laura Elizabeth (2015)
The analysis of the social, economical and financial impact of the irrigation project of the Community of Pisambilla, in the Cayambe Region of the northern area or the Province of Pichincha, is created to offer farmers the opportunity to generate more income and at the same time obtain a larger benefit in the efficient use of the areas resources. Through this mechanism they will understand what benefits they will receive with the implementation of the irrigation system. Based on a technical manner they will be able to take better advantage of the natural resources in the area, maintain their consumers satisfied, increase their income and help in the progress of Cayambe. The idea is to create an operational plan that will help people of the area increase their income, calculate their budget on a short and long term and have control over their cash flow. In essence, this will bring to the community a better lifestyle.